Comparative Analysis of Added Value of Sago-Based Food Products, Biscuit and Bagea Cake - Tarwoyo, Tribudi Prihatini; Umar, Muhammad Agus; Hamadal, Rusdi (Peneliti.net, 2025)
Sago is one of the potential carbohydrate-producing plants in Indonesia that can be used for food diversification. This study aims to analyze the added value of various types of sago products processed by household sago processing industries in Bacan District, Halmahera Selatan Regency. The method used is the determination of informants determined by snowbell sampling (the number depends on the field conditions), namely 5 stakeholder informants consisting of community leaders, entrepreneurs, the Regency Agriculture Office and the Industry and Trade Office, as well as 7 sago processing informants. The analysis used to determine the sago processing industry business used cost, revenue, income, profit, and value-added analysis. With the research results, namely the added value for bagea processing is IDR 11,400 and sago biscuits are IDR 72,400 for each kilogram. Meanwhile, the added value ratio for bagea processing is 81.43% and sago biscuits are 96.53%. This shows that the development of sago processing industries provides positive added value.